Nursing Quality Indicators in Emergency Nursing : A Scoping Review - Mustonen, Meeri; Ameel, Maria; Ritmala, Marita; Leino-Kilpi, Helena (Lippincott, 2025)
Background: Nursing quality indicators (NQIs) are essential for evaluating and managing care, yet few validated NQIs exist for emergency nursing. The dynamic nature of this field demands specific, validated indicators.
Purpose: The purpose of this review was to identify NQIs in adult emergency nursing using Donabedian's quality categories (structure, process, outcome) and explore their validation.
Methods: A scoping review was conducted including articles from 2010 to February 2023, using the Cumulative Index to Nursing and Allied Health Literature and Medline (Ovid) databases.
Results: Among 936 screened articles, 18 were included, identifying 85 NQIs across structure (n = 14), process (n = 45), and outcome (n = 26) in emergency nursing. However, the validation of these NQIs was limited.
Conclusions: NQIs evaluate emergency nursing quality, primarily in process assessment. Future work should validate the NQIs identified in this review for adult emergency nursing and search for potential new ones.